Should interventions to reduce respirable pollutants be linked to tuberculosis control programmes?. Issue 7474 (4th November 2004) - Baris, Enis; Ezzati, Majid
Abstract : The potential benefits of linking tuberculosis control programmes with interventions to reduce smoking and indoor air pollution make research to improve our understanding of their relation a high priority